Factors associated with maintenance of the use of internet, EpiFloripa Idoso longitudinal study - Rodrigo de Rosso Krug; André Junqueira Xavier; Eleonora d'Orsi (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To describe the use of the internet and to identify the sociodemographic and health factors associated with changes in the use of the internet over four years in older adults participating in the Brazilian EpiFloripa Idoso study. METHODS This is a longitudinal home-based, population-based study with 1,197 older adults who live in the urban area of Florianópolis, State of Santa Catarina, Brazil. We applied a face-to-face interview. We describe the use of internet according to frequency, place, devices, and motives of the use of the internet. To identify factors associated with changes in the use of the internet, we categorized the outcome as: non-use of the internet, stopped using the internet, started using the internet, and kept using the internet. The independent variables were sex, age, family income, education level, family arrangement, marital status, presence of caregiver, paid work, and cognitive impairment screening. We used multinomial logistic regression with risk ratio (RR) estimates and their respective confidence intervals (95%CI). RESULTS The prevalence of the use of internet increased from 22.9% in 2009-2010 to 26.6% in 2013-2014. Of the total number of older adults who participated in the study, 7.5% started using the internet, 3.2% stopped using it, 19.1% kept their use, and 70.2% kept their non-use in the analyzed period. Of the older adults who used the internet, most used it every day or almost every day of the week, in their own home, on desktop or portable computers, mainly to send and receive messages, to search for information to learn or investigate something, to find information about goods and services, and to use news, social networking, and health information websites. The factors associated with the use of internet over four years were: being male (RR = 2.19, 95%CI 1.48-3.26), higher monthly family income (RR = 3.53, 95%CI 1.35-9.23), higher education level (RR = 2.64, 95%CI 1.57-4.43), and no presence of caregiver (RR = 0.08, 95%CI 0.02-0.31). CONCLUSIONS Although the use of the internet is increasing among older adults, most of the population is still digitally excluded, especially women with lower income and education level. Strategies that promote the digital inclusion of older adults should be stimulated, aiming to universalize the use of the internet, and they should take into account socioeconomic and gender inequalities.